Strategi Bisnis Usaha Mikro Kecil Menengah (UMKM) Menggunakan Bisns Model Canvas - Nurul Hidayat; Siti Jamilah; Jaharuddin Jaharuddin (Taksasila Edukasi Insani, 2023)
The purpose of the study was to analyze the current business situation, and recommend a new business strategy for improvement. by using Qualitative method using Business Model Canvas and and The novelty of the research is part of the study to enrich various MSME business strategy research in Indonesia. The results of research conducted at the al-hidayat perfume shop pamulang 2 by using the Binis Model Canvas (BMC) at the al-hidayat perfume shop pamulang 2 that the al-hidayat perfume shop pamulang 2 has implemented several points that have been written to the researcher to develop its business. and then SWOT analysis of internal and external factors where each external and internal factor gets a different score where the score obtained by the internal strength factor scores 1.56, the internal weakness factor scores 0.96, the external opportunity factor scores 1.65 and the external threat factor scores 1.19. When viewed from the diagram, the strategy of the pamulang 2 al-hidayat perfume shop is in quadrant one, which means it supports an aggressive strategy. Pamulang 2 al-hidayat perfume shop has the opportunity to develop its business. Keywords : Business model Canvas (BMC), at al-hidayat perfume shop pamulang 2